Do Tax Incentives Moderate the Impact of Cash Flow and Sales Growth on Accounting Conservatism - Erlina Widayanti Djatnicka; Dian Sulistyorini Wulandari; Nur Asti Amalia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates the relationships between cash flow, sales growth, tax incentives, and accounting conservatism. The study reveals that cash flow significantly influences accounting conservatism, indicating that firms with higher cash flows tend to adopt less conservative accounting practices to seize growth opportunities. Additionally, strong sales growth is associated with reduced accounting conservatism, as companies aim to meet market expectations and present favorable financial results. However, the interaction between cash flow and tax incentives, as well as sales growth and tax incentives, does not significantly affect accounting conservatism. These findings suggest that firms prioritize immediate financial performance over tax strategies when making accounting decisions. The research highlights the need to explore further industry-specific factors, long-term effects, and the practical implementation of tax incentives. By addressing these aspects, future studies can provide deeper insights into how financial reporting practices evolve and inform better corporate governance and stakeholder communication. Overall, this research contributes to understanding the dynamics influencing accounting conservatism in a changing economic landscape